Morphological characteristics of the Pterodoras granulosus digestive tube (Valenciennes, 1821) (Osteichthyes, Doradidae) - Germano, Ricardo de Melo; Stabille, Sandra Regina; Mari, Renata de Britto [UNESP]; Bertaglia Pereira, Joice Naiara; Scoz Faglioni, Juliana Raquel; Miranda Neto, Marcilio Hubner de (Wiley-Blackwell, 2014)
Little is known about the digestive tube (DT) morphology of the fish Pterodoras granulosus. Therefore, macro-, meso- and microscopic aspects of 15 P.granulosus DTs were analysed. The muscular layer was composed of striated skeletal muscle in the oesophagus and smooth muscle in the other segments. The epithelium progressed from a stratified pavement in the oesophagus to a simple column in the other segments, with a flat striated border in the intestine. A large number of mucus-secreting periodic acid-Schiff (PAS)-positive cells were observed in the oesophagus. In the stomach, the number of glands in the region decreased towards the cardiac-fundic region, and none were found in the pylorus. The intestine showed an epithelium with absorption cells and an increasing number of PAS-positive caliciform cells towards the distal region. Tests showed that the oesophagus is adapted for passing and preparing food for the chemical digestion that occurs in the stomach, which also has storage functions without grinding action. The proximal intestinal region was consistent with fat absorption, and the medium region, with the absorption of other nutrients. The distal region was short and consistent with a role in absorption for osmoregulation as well as in the formation, storage and disposal of faeces.
Keywords: bone fish; teleost; Siluriformes; morphology; digestive system